METODE ALTERNATIP PEMBELAJARAN MATEMATIKA GEOMETRI RUANG PADA TINGKAT SEKOLAH DASAR MELALUI PONSEL BERBASIS ANDROID - -, Uminingsih (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Learning methods have an important role to the success of student understanding of the learning material presented. In learning methods it is required media in the form of learning applications that can be used to deliver learning materials. Learning applications can use smart mobile phones (HP) to ease and interest the learning process so that the learning objectives ca be achieved. With the launch of Android HP technology where day today, increasingly relatively cheap price so that many people can reach them, including for their children . One of the features that android open source and open-platform does not depend on the manufacturing / certain vendors so it can be used in a wide variety of vendors. Therefore, in this study Android HP was utilized to provide a learning material in space geometry of mathematics that teach how to calculate the volume and area by applying the certain equations for various shapes . The trick is to embed an application program that has been made into HP. With the success of making the media application it is expected to help elementary school students to be more pleasure and easier to memorize mathematic formulas of the learning materials. By using this media through HP, students can learn anywhere, anytime and in any atmosphere.